2022
DOI: 10.1017/sjp.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Involvement in Cybergossip: Influence on Social Adjustment, Bullying and Cyberbullying

Abstract: Gossip is a type of social behavior present in all types of social networks, and cybergossip is an emerging kind of online social behavior which can both promote and hinder relationships between peers. The aim of this study was to explore the relation between involvement in cybergossip and the development of behavior of social adjustment, bullying and cyberbullying (aggression and victimization), based on gender and age. A total of 510 secondary school students (49.4% girls) aged 12 to 17 years old (M = 14.01;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
(75 reference statements)
1
4
0
1
Order By: Relevance
“…Given that peer relationships are particularly important during this part of life (Albert et al, 2013), cybergossip may play a key role in socialization processes. In fact, studies have showed that the frequency of cybergossip is significantly associated with active or passive participation in bullying and/or cyberbullying during adolescence (Falla et al, 2021;Garcia-Fernandez et al, 2022). Similar results have been noted in cohorts of 10-to-13-year-old school children (López-Pradas et al, 2017;Romera et al, 2018).…”
Section: Introduction Internet and The Transformation Of Gossip Into ...supporting
confidence: 71%
“…Given that peer relationships are particularly important during this part of life (Albert et al, 2013), cybergossip may play a key role in socialization processes. In fact, studies have showed that the frequency of cybergossip is significantly associated with active or passive participation in bullying and/or cyberbullying during adolescence (Falla et al, 2021;Garcia-Fernandez et al, 2022). Similar results have been noted in cohorts of 10-to-13-year-old school children (López-Pradas et al, 2017;Romera et al, 2018).…”
Section: Introduction Internet and The Transformation Of Gossip Into ...supporting
confidence: 71%
“…Psychological publications are more likely to identify triggers of aggressive attitudes that have to do with the bully’s family or social context [ 25 ]. On the other hand, there are works focused on analyzing the influence that certain specific factors have on the development of bullying attitudes, such as (i) television watching and the excessive use of video games with violent content [ 28 , 29 ]; (ii) parental behaviors of rejection, chaos, coercion or aggressiveness, which favor the development of bullying attitudes and, above all, cyberbullying in young people [ 27 ]; (iii) pressure from circles of friends and the social context [ 19 , 20 ]; or (iv) the attitude of teachers, which conditions the adoption of the role of bully or victim by students [ 30 ]. As a novel result of the present study, it was found that all these factors are present, in the opinions of teachers and psychologists, in the development of aggressive behavior in early childhood education, but the existence of an action plan against bullying conditions the perception of which factors are considered dominant, which, moreover, are also different among teachers and psychologists ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, studies focused on the analysis of the concentrated locations of harassment show that the most interesting scenario is the school playgrounds [ 18 ]. In them, bullying situations derived from the pressure to demonstrate more power among peers are observed [ 19 , 20 ]. In this sense, it is necessary to describe the personality of the aggressors, who may present diverse characteristics that may include aggressiveness towards the rest of the students and even adults, leadership charisma and strong temperament, observing in most cases an absence of empathy towards the victim [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this point, Íñiguez et al [10] express that traditional bullying continues with cyberbullying, hence the importance of examining the predictors of this behavior. Specifically, in the relationships that take place in the school space, these behaviors of cyberbullying are frequent [11][12][13]. Data on cyberbullying derived from reports prepared by Save the Children [14,15] in Spain indicate that the figures continue to be worrying both for schoolchildren involved in recent months as aggressors (3.3% in cyberbullying) and for those in the role of victim (6.9% in cyberbullying).…”
mentioning
confidence: 99%